New Modeling Concepts for Today<U+0019>s Software Processes International Conference on Software Process, ICSP 2010, Paderborn, Germany, July 8-9, 2010. Proceedings - M<U+00fc>nch, J<U+00fc>rgen.; Yang, Ye.; Schf̃er, Wilhelm. (Lecture Notes in Computer Science, 2010)
This book constitutes the proceedings of the International Conference on New Modeling Concepts for Today's Software Processes, held in Paderborn, Germany in July 2010.